Effect of long-term training on physical and hematological values in young female handball players - Savucu, Yuksel (Academic Journals, 2012)
The aim of the study was to evaluate the effect of long-term handball training on physical and hematological variables in young female handball players. Thirty girls (12.58+/-0.51 year) from different schools and clubs, voluntarily participated in this study for handball training. We found significant differences at height, weight, standing long jump, seated medicine ball throw and 30 m sprint test parameters (P<0.001). We examined the effects between pre-training and post-training values in some hematological parameters and found no significant differences between white blood cell count (WBC), erythrocyte (RBC), hematocrit (HCT), and urea values (P>0.05). However, significant differences was found at aspartate aminotransferase (AST-SGOT), alanine aminotransferase (ALT-SGPT), power of hydrogen (Ph), urine density, mean corpuscular volume (MCV), mean red blood cell distribution width (RDW) and platelet (PLT) values (P<0.05). We found significant differences in hemoglobin (Hgb), creatine, fasting blood glucose, mean corpuscular volume (MCH), mean hemoglobin concentration (MCHC) and mean platelet volume (MPV) values (P<0.001). Research findings were obtained by using paired t test. In conclusion, significant effects were observed in some physical and physiological developments of girls. Especially, the girls who were selected for handball achieved major degree at the end of young women's Championships.
Keywords: Handball; training; female; blood